2013
DOI: 10.1177/1525740113484965
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Speech Sound Intervention Delivered by Telepractice and Side-by-Side Service Delivery Models

Abstract: Telepractice has the potential to provide greater access to speech-language intervention services for children with communication impairments. Substantiation of this delivery model is necessary for telepractice to become an accepted alternative delivery model. This study investigated the progress made by school-age children with speech sound impairments in side-by-side intervention compared with telepractice intervention. Fourteen children aged 6 through 10 years with identified speech sound disorders were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 16 publications
6
72
1
3
Order By: Relevance
“…These results are in line with those reported by Waite and colleagues 11 in their study of [5][6][7][8][9] year-olds whose language was assessed using the CELF-4 via telehealth. Their study found very good agreement between telehealth and face-to-face scorers when assessing children using custom built equipment in a university setting, with some variation between subtests (k range from 0.93 to >0.99).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are in line with those reported by Waite and colleagues 11 in their study of [5][6][7][8][9] year-olds whose language was assessed using the CELF-4 via telehealth. Their study found very good agreement between telehealth and face-to-face scorers when assessing children using custom built equipment in a university setting, with some variation between subtests (k range from 0.93 to >0.99).…”
Section: Discussionsupporting
confidence: 94%
“…9 Yet despite evidence for its utility in delivering interventions, only a small number of studies have examined the role for telehealth in standardised language assessment. Language assessments are crucial in establishing diagnoses, guiding intervention and documenting progress in children with language difficulties.…”
Section: Telehealth In Speech-language Pathologymentioning
confidence: 99%
“…Following a stable baseline, participants had staggered entry into the intervention phase of the study in which data were collected continuously for 12 weeks. Further, staggered entry into the intervention phase was determined based on a set number of days (Gast et al, 2013), with each dyad entering the intervention phase after the previous dyad completed 3 weeks of intervention. Thus, Dyads 1, 2, and 3 completed 5, 7, and 9 baseline sessions, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…McDuffie et al (2013) found that targeted parent behaviors were used as frequently during video-conferencing sessions as they were during face-to-face sessions conducted in the clinic. A study by Grogan-Johnson et al (2013) found no significant differences between face-to-face and distance delivery of an intervention on the degree of improvement in speech sound production in school-aged children. Further, work by Wainer and Ingersoll (2015) found significant gains in parents’ use of intervention strategies aimed at increasing imitation in children with ASD through a parent-training paradigm administered through online training.…”
Section: Introductionmentioning
confidence: 95%
“…). The participants in Grogan‐Johnson et al.’s () study had articulation and phonological disorders rather than CAS (S. Grogan‐Johnson, personal communication, 6 February 2015) and therefore these findings cannot necessarily be applied to children with CAS. Effective treatments for CAS often focus on prosody or speech movements (Maas et al .…”
Section: Introductionmentioning
confidence: 97%